(DON’T) HOLD YOUR BREATH: THE SOUTH AFRICAN COVID-19 VACCINE APPROVAL PROCESS AND REGULATORY FRAMEWORK - Larisse Prinsen (Obiter, 2021)
The world seemed to sigh in relief in early November 2020, when it was announced that the Covid-19 vaccine developed by Pfizer and BioNTech showed itself to be 90 per cent effective in early data analysis. This announcement was followed by one from Moderna Inc that its vaccine in development was showing to be almost 95 per cent effective. Soon after, numerous other companies announced the efficacy of their respective vaccines and roll-out plans and policies were made and even implemented. However, this sigh of relief was perhaps premature. Although these announcements were good news on the face of it, they also brought to light some concerns. The fast pace at which the vaccines were developed and made available for human use raises various ethical and legal issues as well as questions related to the safety and efficacy thereof. The correct dosage and timing of vaccination is still not fixed, vaccine expiration periods and the discovery of new variants of the Covid-19 virus has further added to these concerns. In addition, uncertainty exists regarding the approval process that should be followed for these vaccines. This last concern forms the focus of this note.